Kampanye Humas BNNK Surabaya Melalui Program Cak Sunar - Nurmala Zanni Yudha Reswari (CV. ITTC INDONESIA, 2026)
This study aims to analyze the public relations campaign conducted by the Surabaya City National Narcotics Agency (BNNK Surabaya) through the Cak Sunar Program as an effort to prevent drug abuse. This research employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation involving public relations officers of BNNK Surabaya and parties involved in the implementation of the Cak Sunar Program. The results indicate that the public relations campaign of BNNK Surabaya is carried out by delivering educational and persuasive messages regarding the dangers of drug abuse using communicative and easily understood language. The Cak Sunar Program functions as a medium for socialization and education, particularly targeting young people. However, the implementation of the campaign still faces several challenges, such as limited audience reach and insufficient activity intensity. Therefore, strengthening public relations campaign strategies is necessary to ensure that drug abuse prevention messages can be delivered more effectively and sustainably to the wider community.